Mass independent sulfur isotope signatures in CMs: Implications for sulfur chemistry in the early solar system. (1st January 2017) - Labidi, J.; Farquhar, J.; Alexander, C.M.O'D.; Eldridge, D.L.; Oduro, H.
Abstract: We have investigated the quadruple sulfur isotopic composition of inorganic sulfur-bearing phases from 13 carbonaceous chondrites of CM type. Our samples include 4 falls and 9 Antarctic finds. We extracted sulfur from sulfides, sulfates, and elemental sulfur (S 0 ) from all samples. On average, we recover a bulk sulfur (S) content of 2.11 ± 0.39 wt.% S (1σ). The recovered sulfate, S 0 and sulfide contents represent 25 ± 12%, 10 ± 7% and 65 ± 15% of the bulk S, respectively (all 1σ). There is no evidence for differences in the bulk S content between falls and finds, and there is no correlation between the S speciation and the extent of aqueous alteration. We report ranges of Δ 33 S and Δ 36 S values in CMs that are significantly larger than previously observed. The largest variations are exhibited by S 0, with Δ 33 S values ranging between −0.104 ± 0.012‰ and +0.256 ± 0.018‰ (2σ). The Δ 36 S/ 33 S ratios of S 0 are on average −3.1 ± 1.0 (2σ). Two CMs show distinct Δ 36 S/ 33 S ratios, of +1.3 ± 0.1 and +0.9 ± 0.1. We suggest that these mass independent S isotopic compositions record H2 S photodissociation in the nebula. The varying Δ 36 S/Δ 33 S ratios are interpreted to reflect photodissociation that occurred at different UV wavelengths. The preservation of these isotopic features requires that the S-bearing phases were heterogeneously accreted to the CM parent body. Non-zero Δ 33 S values are also preserved in sulfide and sulfate, and are positively correlated with S 0 values. This indicates a genetic relationship between the S-bearing phases: We argue that sulfates were produced by the direct oxidation of S 0 (not sulfide) in the parent body. We describe two types of models that, although imperfect, can explain the major features of the CM S isotope compositions, and can be tested in future studies. Sulfide and S 0 could both be condensates from the nebula, as the residue and product, respectively, of incomplete H2 S photodissociation by UV light (wavelength <150 nm). This idea requires that FeS formation and the S 0 condensation co-occur. As an alternative, ice accretion to the CM parent body could allow the delivery of S-MIF in CMs. In that case, sulfides would have been the only S-bearing condensate in CM precursors, and S 0 would have been derived from the oxidation of H2 S trapped in ices, after its photodissociation at low temperature (<500 K) in the nebula. In our models, the observations of H2 S UV photodissociation is required to occur at the disk surface, and allowed in nebular environments with canonical C/O ratios. Vertical motions in the disk would redistribute phases that condensed at high altitude to the midplane, where they accreted in the phases that make up the chondritic matrix.